A functional interaction between hepatic estrogen receptor-α and PNPLA3 p.I148M inherited variant drives fatty liver disease susceptibility in women. (March 2023) - Cherubini, A.; Ostadreza, M.; Jamialahmadi, O.; Pelusi, S.; Rrapaj, E.; Casirati, E.; Passignani, G.; Baselli, G.; Ronzoni, L.; Dongiovanni, P.; Prati, D.; Romeo, S.; et al.
Abstract : Introduction: Fatty liver disease (FLD) related to metabolic dysfunction and excessive alcohol affects almost one third of the global population and is a leading cause of liver related mortality. The PNPLA3 p.I148M variant accounts for the largest fraction of FLD heritability. Although women are protected during the reproductive age, especially after menopause some are susceptible to FLD, but this sexual dimorphism is neglected in clinical studies. The aim was to examine the PNPLA3 p.I148M*female sex interaction in FLD development, and to investigate the underlying mechanism. Methods: The female sex* PNPLA3 p.I148M interaction on FLD was tested in the Liver Biopsy (n=1861), severe FLD case-control (n=4374), Liver-Bible-2021 (n=817) and UK Biobank (n=347, 127) cohorts. PNPLA3 expression was determined in transcriptomic cohort (n=107). HepG2 cells were used for estrogen receptor (ER) modulation and fatty acid treatment, and to generate PNPLA3-ER element (ERE) knock-out clones. Results: In all cohorts we observed an interaction between female sex and PNPLA3 p.I148M, but not other FLD genetic risk variants, in determining FLD development and progression, with a larger effect in postmenopausal women (p<0.05). Higher hepatic PNPLA3 mRNA expression was independently associated with the p.I148M variant and female sex (p=0.002 and p=0.007, respectively). At chromatin immunoprecipitation, ERα agonists induced the ER binding to a specific ERE at a PNPLA3 enhancer site, enhancing its transcriptional activity at luciferase assays. PNPLA3 mRNA and protein expression was upregulated via direct ERα agonists, leading to intracellular fat accumulation in p.I148M homozygous HepG2 cells, but not in wild-type hepatocytes. Genetic deletion of the PNPLA3-ERE by Crispr/Cas9 editing in HepG2 abolished the ERα-induced PNPLA3 and intracellular lipid accumulation in response to fatty acids. Conclusions: We identified a driver of FLD acceleration occurring in a subset of women with metabolic dysfunction at menopause, highlighting at the same time a therapeutic target of particular relevance.